PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) UNTUK MENINGKATKAN KEJUJURAN DAN PRESTASI BELAJAR - Relinda Sirait (DIADIK, 2023)
This study purpose to describe the application of the learning model VCT to improve honesty, learning achievement , and the application of an effective learning model to improve learning achievement compared to learning that does not use the model VCT. The research method used isClassroom Action Research and uses Quasi Experiments. The subjects of this study were students of class X SMA Negeri 3 in Rejang Lebong in the first semester of the 2021/2022 academic year. The number of students in the experimental class, namely class X IPA 1, which amounted to 35 students, for the control class, namely X IPA 3, which amounted to 35 students. The method used in collecting data in this study used learning observation sheets, honesty observation sheets and student achievement tests. Data analysis used the analysis of the average data score and the t-test which consisted of a difference test between cycles and a difference test of two unrelated samples. The results showed that the application of thelearning model VCT could increase students' honesty, learning achievement and the application of thelearning model was VCT effective for improving learning achievement in Civics subjects for class X SMA Negeri 3 in Rejang Lebong.